Tri-metal phosphide as well as preparation method and application thereof
The preparation of trimetal phosphides on the stainless steel mesh substrate by electrochemical deposition method has solved the problem of insufficient catalytic effect, activity and stability of existing transition metal phosphides under alkaline conditions, and achieved good catalysis under alkaline conditions Effect and stability, suitable for high-performance catalysts for electrolyzing water to produce hydrogen.
Patent Information
- Application Number
- CN202411547219.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing transition metal phosphides have insufficient catalytic effect, activity and stability under alkaline conditions, making it difficult to meet the needs of commercialization and scale.
The trimetal phosphide is prepared on the stainless steel mesh substrate by electrochemical deposition. The specific steps include pretreatment and electrochemical deposition of the stainless steel mesh. The molar ratio of Ce, Fe, Ni and phosphorus is 0.75:21.5:30:(10 -40), preferably 0.75:21.5:30:30, the metals in the electrodeposition fluid are cerium, iron and nickel, and the phosphorus source is NaH2PO2·H2O. The electrochemical deposition process uses cyclic voltammetry, and the voltage is set to -1.2 V to -0.6V.
The prepared trimetal phosphide has good catalytic effect, activity and stability under alkaline conditions, can optimize reaction kinetics and reaction thermodynamics problems, and is suitable for high-performance catalysts for hydrogen production by electrolyzing water.
Smart Images

Figure CN119392296A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytic hydrogen production, and in particular relates to a trimetallic phosphide and a preparation method and application thereof. Background Art
[0002] In today's energy shortage, researchers in the field of electrocatalyst hydrogen evolution (HER) catalysts have been working hard to find a catalyst that is cheaper, easier to make, highly stable, safe, environmentally friendly, and efficient when facing complex environmental reactions, which is conducive to the industrialization of hydrogen production by water electrolysis. This helps researchers obtain environmentally friendly energy, thereby effectively solving energy and environmental problems caused by the shortage of fossil energy and its use. There are three main categories of catalysts known at present: the first category is precious metal catalysts, such as Pt, Ru, Pd and other metals with high stability. Due to their good catalytic activity and excellent conductivity, they have been favored by researchers, but due to their high price, they have never been applied to the process of industrialization; the second category is transition metal-based catalysts that are cheaper than the above precious metals, obtained by researchers based on long-term experiments. According to their chemical characteristics and the combination ratio between components, they can be subdivided into: alloys, phosphides, sulfides, nitrides, carbides and other catalysts, which also have good hydrogen evolution reaction activity. These metal catalysts have many advantages such as lower cost, easy to control appearance, and adjustable ratio. No matter what electrolyte solution they are placed in, they have excellent catalytic effects; the third category is non-metallic catalysts. At present, in addition to combining and doping metal and non-metallic elements, the treatment methods have also been improved to varying degrees. In synthesizing transition metal catalysts, the preparation methods adopted by technicians in this field are usually hydrothermal or calcination methods, introducing sulfur sources or phosphorus sources, etc. These methods take a long time to prepare catalysts, have high trial and error costs, and are also prone to produce gases that pollute the environment, posing a potential safety threat to experimenters.
[0003] At the same time, existing transition metal phosphides have some defects under alkaline conditions (for example, the catalytic effect, activity and stability of transition metal phosphides under alkaline conditions cannot meet the requirements), and these defects make them unable to meet the needs of commercialization and scale-up.
[0004] Therefore, it is necessary to find a material for producing hydrogen by electrolysis of water that is most cost-effective, has the simplest synthesis method, and has excellent catalytic performance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a trimetallic phosphide and a preparation method and application thereof. The trimetallic phosphide of the present invention can be used as a high-performance water electrolysis catalyst that simultaneously optimizes reaction kinetics and reaction thermodynamics problems.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] The present invention provides a method for preparing trimetallic phosphides, using a stainless steel mesh as a substrate and utilizing an electrochemical deposition method to prepare trimetallic phosphides;
[0009] The metals in the electrochemical deposition solution are cerium (Ce), iron (Fe) and nickel (Ni). Further, the molar ratio of Ce, Fe, Ni and phosphorus is 0.75:21.5:30:(10-40), preferably 0.75:21.5:30:30.
[0010] Furthermore, the electrochemical deposition process adopts cyclic voltammetry, and the voltage is set to -1.2V to -0.6V.
[0011] Furthermore, the preparation method of the trimetallic phosphide comprises the following steps:
[0012] Pre-treat the stainless steel mesh;
[0013] Cyclic voltammetry was used to perform electrochemical deposition on the pretreated stainless steel mesh with a voltage set between -1.2 V and -0.6 V.
[0014] Furthermore, the process of pre-treating the stainless steel mesh is as follows:
[0015] The stainless steel mesh was cut into 1 cm × 2.5 cm and polished with sandpaper. The polished stainless steel mesh was placed in hydrochloric acid and ultrasonicated for 30 min. Then, it was ultrasonicated with anhydrous ethanol and water for 20 min respectively, and finally dried.
[0016] Furthermore, the mesh number of the stainless steel mesh is 600-2000 mesh, preferably 600 mesh, 1200 mesh, 1400 mesh or 2000 mesh, and more preferably 1400 mesh.
[0017] Furthermore, the process of pre-treating the stainless steel mesh is as follows:
[0018] A stainless steel mesh (1400 mesh) was prepared and cut into 1 cm × 2.5 cm as a conductive substrate. In order to ensure the generation of more active sites, the conductive substrate stainless steel mesh was polished using 400-mesh sandpaper. First, the polished stainless steel mesh was soaked in a 3 mol / L hydrochloric acid solution and ultrasonicated for 30 min to remove inorganic impurities and oxidized parts on the surface. The treated substrate was placed in anhydrous ethanol and ultrasonicated for 20 min to remove organic impurities on the conductive substrate. Finally, the treated substrate was placed in deionized water for ultrasonic washing for 20 min, and finally taken out and dried in a vacuum drying oven for use.
[0019] Furthermore, the number of cycles of the electrochemical deposition is 14-42 cycles (CV), preferably 14 cycles, 28 cycles, 35 cycles or 42 cycles, and more preferably 35 cycles.
[0020] Furthermore, the phosphorus (P) source in the electrolyte during electrochemical deposition is NaH2PO2·H2O.
[0021] Furthermore, in order to avoid oxidation of the deposited iron in the air, a drying process is performed after the electrochemical deposition is completed.
[0022] Furthermore, the process of electrochemical deposition is:
[0023] 0.75mmol Ce(NO3)2·6H2O, 21.5mmol FeSO4·7H2O, 30mmol Ni(NO3)2·6H2O, 30mmol NH4F and 30mmol NaH2PO2·H2O were dissolved in 50mL of deionized water as the electrodeposition solution;
[0024] Cyclic voltammetry was used to perform electrochemical deposition on the pretreated stainless steel mesh with a voltage set at -1.2 V to -0.6 V. After the electrochemical deposition, the mesh was dried.
[0025] The present invention uses multiple types of transition metals and P to work together, and the obtained trimetallic phosphide has stronger catalytic performance than single metal doping or bimetallic phosphide. Ce, as one of the most abundant rare earth metal elements, has a special orbital structure, not only has strong oxygen affinity, but also has good electrical conductivity. The addition of Ce in the present invention stimulates the hydrogen evolution ability of the catalyst. In the trimetallic phosphide of the present invention, the effects of metal and P are different and complementary, and the ratio of metal and P will affect the catalytic activity of the catalyst.
[0026] The second technical solution of the present invention:
[0027] The present invention also provides a trimetallic phosphide prepared by the above method, which can be used as a high-performance water electrolysis catalyst for simultaneously optimizing reaction kinetics and reaction thermodynamics.
[0028] The third technical solution of the present invention:
[0029] The present invention also provides the use of the trimetallic phosphide in producing hydrogen by electrolyzing water.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] (1) The preparation method of the trimetallic phosphide of the present invention is simple and environmentally friendly, and can meet the needs of commercialization and scale-up;
[0032] (2) The trimetallic phosphide of the present invention can be used as a high-performance water electrolysis catalyst that optimizes both reaction kinetics and reaction thermodynamics. When the current density is 10 mV·cm -2 When the overpotential is 61.6mV, the impedance value is the smallest, and the Tafel slope value is 34mV·dec -1 , the double layer capacitance is 53.2mF·cm -2 , has good catalytic effect, activity and stability under alkaline conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0034] Figure 1 C for Ni / Ce / Fe / P-14CV, Ni / Ce / Fe / P-28CV, Ni / Ce / Fe / P-35CV, Ni / Ce / Fe / P-42CV dl Value graph (a) and EIS graph (b);
[0035] Figure 2 CV curves with scanning cycles of Ni / Ce / Fe / P-14 (a), Ni / Ce / Fe / P-28 (b), Ni / Ce / Fe / P-35 (c), and Ni / Ce / Fe / P-42 (d);
[0036] Figure 3 The Tafel slope of trimetallic phosphide samples at different scanning numbers (a) and the LSV graph of trimetallic phosphide samples at different scanning numbers (b);
[0037] Figure 4 Ni / Ce / Fe / P-600 mesh (600 mesh), Ni / Ce / Fe / P-1400 mesh (1400 mesh), Ni / Ce / Fe / P-1600 mesh (1600 mesh), Ni / Ce / Fe / P-2000 mesh (2000 mesh) dl Value graph (a) and EIS graph (b);
[0038] Figure 5 Electrode materials of Ni / Ce / Fe / P-600 mesh (a), Ni / Ce / Fe / P-1400 mesh (b), Ni / Ce / Fe / P-1600 mesh (c), and Ni / Ce / Fe / P-2000 mesh (d) were prepared in 1M KOH solution at scan rates of 10, 20, 30, 40, and 50 mV·s -1 CV curve of
[0039] Figure 6 The Tafel slope of trimetallic phosphide samples at different scanning numbers (a) and the LSV graph of trimetallic phosphide samples at different scanning numbers (b);
[0040] Figure 7 C for Ni / Ce / Fe / P-10mmol, Ni / Ce / Fe / P-20mmol, Ni / Ce / Fe / P-30mmol, Ni / Ce / Fe / P-40mmol dl Value graph (a) and EIS graph (b);
[0041] Figure 8 Electrode materials of Ni / Ce / Fe / P-10mmol(a), Ni / Ce / Fe / P-20mmol(b), Ni / Ce / Fe / P-30mmol(c), and Ni / Ce / Fe / P-40mmol(d) were dissolved in 1M KOH solution at scan rates of 10, 20, 30, 40, and 50 mV·s -1 CV curve of
[0042] Fig. 9 The Tafel slope of trimetallic phosphide samples at different scanning numbers (a) and the LSV graph of trimetallic phosphide samples at different scanning numbers (b);
[0043] Fig.10 This is the stability of the trimetal phosphide in Example 1. DETAILED DESCRIPTION
[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] All raw materials used in the examples of the present invention are commercially available.
[0050] The technical solution of the present invention is further illustrated by the following embodiments.
[0051] Example 1
[0052] Pretreatment of stainless steel mesh: Prepare a 1400 mesh stainless steel mesh and cut it into 1cm×2.5cm as a conductive substrate. In order to ensure the generation of more active sites, use 400 mesh sandpaper to polish the conductive substrate stainless steel mesh. First, soak the polished stainless steel mesh in a 3mol / L hydrochloric acid solution and ultrasonicate for 30 minutes to remove inorganic impurities and oxidized parts on the surface. Then, place the treated substrate in anhydrous ethanol and ultrasonicate for 20 minutes to remove organic impurities on the conductive substrate. Finally, place the treated substrate in deionized water for ultrasonic washing for 20 minutes, and finally take it out and dry it in a vacuum drying oven for use.
[0053] Electrochemical Deposition:
[0054] 0.75mmol Ce(NO3)2·6H2O, 21.5mmol FeSO4·7H2O, 30mmol Ni(NO3)2·6H2O, 30mmol NH4F and 30mmol NaH2PO2·H2O were dissolved in 50mL of deionized water as the electrodeposition solution;
[0055] Cyclic voltammetry was used to set the voltage to -1.2 V to -0.6 V, and electrochemical deposition was performed on the pretreated stainless steel mesh. The number of electrochemical deposition cycles was 35 cycles. After the electrochemical deposition, the mesh was dried to obtain a trimetallic phosphide, which was recorded as Ni / Ce / Fe / P-35CV (Ni / Ce / Fe / P-1400 mesh, Ni / Ce / Fe / P-30mmol).
[0056] Example 2
[0057] Same as Example 1, except that the mesh number of the stainless steel mesh is 600 mesh, denoted as Ni / Ce / Fe / P-600 mesh.
[0058] Example 3
[0059] Same as Example 1, except that the mesh number of the stainless steel mesh is 1200 mesh, which is recorded as Ni / Ce / Fe / P-1200 mesh.
[0060] Example 4
[0061] Same as Example 1, except that the mesh number of the stainless steel mesh is 2000 mesh, which is recorded as Ni / Ce / Fe / P-2000 mesh.
[0062] Example 5
[0063] Same as Example 1, except that the amount of NaH2PO2·H2O in the electrodeposition solution is 10 mmol, recorded as Ni / Ce / Fe / P-10 mmol.
[0064] Example 6
[0065] Same as Example 1, except that the amount of NaH2PO2·H2O in the electrodeposition solution is 20 mmol, recorded as Ni / Ce / Fe / P-20 mmol.
[0066] Example 7
[0067] Same as Example 1, except that the amount of NaH2PO2·H2O in the electrodeposition solution is 40 mmol, recorded as Ni / Ce / Fe / P-40 mmol.
[0068] Example 8
[0069] The same as Example 1, except that the number of electrochemical deposition cycles is 14, denoted as Ni / Ce / Fe / P-14CV.
[0070] Example 9
[0071] The same as Example 1, except that the number of electrochemical deposition cycles is 28, denoted as Ni / Ce / Fe / P-28CV.
[0072] Example 10
[0073] Same as Example 1, except that the number of electrochemical deposition cycles is 42, denoted as Ni / Ce / Fe / P-42CV.
[0074] Before the electrochemical data collection work begins, the first preparation work is to pre-treat the glassy carbon electrode to effectively improve the sensitivity of the electrode in the electrochemical reaction and improve the accuracy of the test sample. In this type of operation, the suede and aluminum oxide polishing powder, distilled water, etc. required for polishing the glassy carbon electrode must be prepared first. The specific steps are to evenly sprinkle the polishing powder on the round suede, add a small amount of distilled water, stir with the insulating part of the glassy carbon electrode, and fully mix the water and aluminum oxide polishing powder to form a uniform slurry. Hold the glassy carbon electrode, keep your wrist still, and use your arm to make the suede and the broken carbon electrode surface perpendicular, slowly and evenly, and move vertically on the suede surface filled with aluminum oxide polishing powder slurry to form an "8" grinding path. Remember not to change the path to a parallel "1", which will cause scratches on the electrode surface. Then rinse the polished glassy carbon electrode with distilled water. First, check whether there are scratches on the surface. If there are, continue to polish it until it is smooth. If there are no scratches visible to the naked eye, place it in ultrasonic water for cleaning for 2 to 3 minutes, and repeat 3 times.
[0075] After the cleaning work is completed, switch the electrochemical workstation to cyclic voltammetry mode, use a mixed solution of 0.2M KNO3 and 0.01MK3Fe(C2N)6, set the scanning voltage to 0-0.6V, and the scanning speed to 50mV / s. When the peak difference of the scanned image is less than 80mV, the next formal experimental measurement work can be carried out. If the value is greater than 80mV, the polishing will be repeated until the test result meets the standard before the next step can be carried out.
[0076] The three-electrode system was tested at room temperature and pressure. Before the measurement, a 1 mol / L (pH = 14) potassium hydroxide solution was prepared as the electrolyte solution for the electrode reaction in this experiment. The working electrode was prepared in a size of 1 cm × 3 cm. The prepared working electrode sample was wrapped with plastic wrap to form a square with a side length of 1 × 1 cm, so that the area reached 1 cm -2 It is convenient for data calculation. With Pt electrode as counter electrode and Hg / HgO electrode as reference electrode, after all the test instruments are in place, high-purity nitrogen should be introduced into the system for 15 minutes to exhaust the air in the system, so that the experiment can be carried out more safely in an inert atmosphere. Prepare a magnet to stir the 1M KOH solution at a low speed to prevent the generated gas from being unable to desorb in time.
[0077] After the above preparations are completed, iR compensation should be performed first, and then the sample should be activated by voltammetry for 5 cycles, and then linear sweep voltammetry (LSV) should be performed. The scanning rate should be set to 5 mV·s -1 The value of electrochemical impedance spectroscopy (EIS) is set at an open circuit voltage of 3 mV, and the LSV curve is used to find the flat area where no redox reaction occurs. The scanning speed of CV is: 10-50 mV·s -1 The curve of current density changing with time, when the current density is 10mA·cm -2 The chronoamperometric measurement was performed at the corresponding potential. The stability of the sample was measured by chronoamperometric method and could be maintained for 24 hours continuously. The Tafel slope value was obtained from the LSV curve.
[0078] like Figure 1 As shown, Figure 1 (a) shows the double-layer current charge and discharge of the trimetallic phosphide Ni / Ce / Fe / P at 14, 28, 35, and 42 scans. The value of the potential range is the value of the non-Faraday current interval where no electrochemical reaction occurs and no redox reaction occurs. This is the only way to more accurately derive the double-layer capacitance. (b) shows the corresponding electrochemical impedance at the above different scans. The catalyst composed of three different metals, Ni, Ce, and Fe, will form a covalent bond. Under the synergistic effect of the three, when the same mass of NaH2PO2·H2O is added as a phosphorus source, the Figure 1 It can be observed that the trimetallic phosphide sample with 35 scans has the most outstanding catalytic effect among the four different variables. The slope obtained after linear fitting of the difference of the cyclic voltammetry curve is the largest, which is 5 times that of the scans with 14 scans, and 2 times that of the scans with 28 and 42 scans. The working electrode has a very obvious catalytic effect advantage. Figure 1 In the electrochemical impedance spectrum (b), it can be seen that the EIS with 28 scans has a larger semicircle arc, which means that during the electrochemical reaction, the sample with 28 scans is less likely to be polarized than the sample with a smaller arc. Figure 1 In (b), the impedance results of the 35-turn and 42-turn scans are very close, but the arc of the EIS graph of the sample with 35 turns is always directly below the 42-turn scan, indicating that the 35-turn sample corresponds to a smaller charge transfer resistance (R ct ), corresponding to Figure 1 The value of the arc's ordinate in (b). Figure 1In (b), the sample with 14 cycles has the largest impedance, followed by the sample with 28 cycles. The main reason for this result may be related to the number of active sites formed on the working electrode substrate when the working electrode sample is made by electrochemical deposition. When the number of scanning cycles is relatively small, the number of reactive particles deposited on the surface of the substrate material is small, and the corresponding number of active sites is small. The deposited particles cannot be evenly and fully distributed on the surface of the electrode material, and the overall active area is small; the impedance data results displayed are large. However, the number of scanning cycles cannot be too many, otherwise it will cause too many particles on the surface to agglomerate and clog the gaps of the stainless steel mesh, which will cause a reduction in the gaps, thereby reducing the relative surface area, and the relative contact area between the solution and the catalyst surface will be reduced, which will lead to a decrease in the catalytic effect. Only an appropriate number of deposition cycles can bring a suitable number of particles to the substrate surface, and the corresponding electrocatalytic hydrogen evolution reaction can proceed faster.
[0079] The CV curves of Ni / Ce / Fe / P-14 (a), Ni / Ce / Fe / P-28 (b), Ni / Ce / Fe / P-35 (c), and Ni / Ce / Fe / P-42 (d) are shown in Figure 2. Figure 2 ; The Tafel slope (a) of the trimetallic phosphide samples with different scanning numbers and the LSV diagram (b) of the trimetallic phosphide samples with different scanning numbers are shown in Figure 3 .from Figure 2 It can be observed that Ni / Ce / Fe / P prepared at different scanning times showed a larger electrochemical active area at 35 scanning times, which also means that Ni / Ce / Fe / P has a larger active area. Figure 3 It can be seen that among all the catalytic electrode materials with scanning cycles, at 35 cycles, when the current density is 10 mA cm -2 When the current density reaches 10 mA·cm -2 The overpotential is 64mV, which is closest to the curve of the standard glassy carbon electrode. Figure 3 In (b), we can more clearly see that the Tafel slope corresponding to the sample scanned 35 times is the smallest, which is 38.7 mV·dec. -1 , showing that the material itself has good HER kinetics. It is intuitively understood that the sample that scanned 35 times has a faster reaction rate during the electrochemical reaction, the faster the charge moves, and only a small overpotential is required to achieve the same current density in the reaction, which means that the electrode material that scanned 35 times participates in the catalytic reaction with a faster electron transfer rate. In summary, the electrode material prepared under the condition of scanning 35 times has a larger active area and a larger number of active sites, and the transition metal phosphides participating in the reaction are evenly deposited on the stainless steel mesh substrate.
[0080] Figure 4 (a) shows the different double-layer capacitance values corresponding to Ni / Ce / Fe / P when using different mesh stainless steel mesh substrates of 600 mesh, 1400 mesh, 1600 mesh, and 2000 mesh as the skeleton; (b) shows the electrochemical impedance corresponding to the above different mesh substrates. When the phosphorus source is NaH2PO2·H2O of the same mass, the number of deposition turns is selected as 35 turns. The catalytic effect when using 1400 mesh stainless steel mesh as the substrate is the most obvious among all meshes. It can be seen that the double-layer capacitance value of 1400 mesh stainless steel mesh is twice that of 1600 mesh stainless steel mesh, and the charge movement on the interface is also faster. When 1600 mesh stainless steel mesh is used as the substrate in the electrode reaction, the electron transfer in the electrochemical reaction is constrained. It may be that the mesh size is too large, resulting in the metal deposited on the surface of the 1600 mesh stainless steel mesh blocking the gaps between the mesh surfaces after the electrodeposition is completed, resulting in a decrease in the relative specific surface area of the electrode and a decrease in the relative contact area with the solution. Compare again Figure 4 In the electrochemical impedance spectrum of (b), the electrochemical impedance of the 600-mesh stainless steel mesh corresponding to the 1400-mesh stainless steel mesh substrate can be observed. The 600-mesh stainless steel mesh has the largest radius in the electrochemical impedance spectrum among all mesh sizes, and the remaining impedance radii are all smaller than 600 mesh. The gaps in the substrate with a smaller mesh size are larger, and the relative surface area of the stainless steel mesh is smaller, which means that the amount of metal attached to the substrate through electrochemical deposition is less. On the other hand, the impedance comparison between 1600 mesh and 2000 mesh may be mainly due to the fact that the 2000-mesh stainless steel mesh substrate material has more relative surface area than the 1600-mesh stainless steel mesh, providing more opportunities for the deposited metal elements to attach, and thus it will be more evenly distributed on the surface of the electrode material than the 1600-mesh stainless steel mesh. In general, when selecting a substrate material, one should not choose a material with a relatively small mesh size only because of price considerations, which would result in the substrate material being unable to provide sufficient adhesion area for the deposited metal material. This would cause an effective number of catalysts to be stacked, and the relative contact area between the solution and the catalyst surface would be very small, thereby reducing the catalytic effect of the reaction. One should not only consider the relative area size and ignore the positive effect of the voids on the catalytic effect.
[0081] Electrode materials of Ni / Ce / Fe / P-600 mesh (a), Ni / Ce / Fe / P-1400 mesh (b), Ni / Ce / Fe / P-1600 mesh (c), and Ni / Ce / Fe / P-2000 mesh (d) were dissolved in 1M KOH solution at scan rates of 10, 20, 30, 40, and 50 mV·s -1 The CV curve is shown in Figure 5 , Figure 5It was observed that the Ni / Ce / Fe / P prepared on stainless steel mesh substrates with different mesh sizes showed a larger electrochemical active area on the Ni / Ce / Fe / P formed on a 1400-mesh stainless steel mesh substrate, which also means that the 1400-mesh Ni / Ce / Fe / P has better catalytic activity for hydrogen production by water electrolysis.
[0082] Figure 6 In (b), the measured data is the same mass of NaH2PO2·H2O. When the scanning number is 35, the LSV graph shows that the curve of 1400 mesh is at the bottom among the four curves of different mesh sizes. According to the experimental data, when the electrochemical reaction is carried out in 1MKOH solution, when the current density reaches 10mA·cm -2 , the overpotential is 64mV. Figure 6 In (a), the 1400 mesh stainless steel mesh substrate can be observed more clearly, and the corresponding Tafel slope is the smallest, which is 41.7 mV·dec. -1 It shows that the material itself has good HER kinetics, and it can be more intuitively understood that the electrochemical reaction is faster when the 1400 mesh stainless steel mesh is used as the substrate. Compared with the substrate materials with other mesh sizes, the charge moves faster. When the same current density is reached in the reaction, only a small overpotential is required, which means that the electron transfer rate of the electrode material with a 1400 mesh substrate participating in the catalytic reaction is faster than that of the other three. In summary, the electrode material prepared with a 1400 mesh substrate has a larger active area and more active sites; the transition metal phosphides participating in the reaction have a sufficiently uniform deposition amount on the stainless steel mesh substrate, and there will be neither a situation where the active surface area is insufficient due to too many substrate voids, nor a situation where the relative surface area of the solution and the catalytic material is reduced due to too few voids. The appropriate amount of substrate mesh can allow the electrode material to have an appropriate amount of void size and quantity on the surface after electrochemical deposition to more fully contact the solution, thereby enhancing the catalytic ability of the catalyst to electrolyze water and hydrogen.
[0083] Figure 7 The main discussion is to verify the effect of adding different molar masses of NaH2PO3·H2O on the catalytic performance of the catalyst under 35 scanning circles with a 1400 mesh stainless steel mesh base material. Figure 7 (b) shows the electrochemical impedance of different masses of NaH2PO3·H2O. Figure 7In (a), the addition of 30mmolNaH2PO3·H2O is most beneficial to the overall catalytic effect of Ni / Ce / Fe / P, and the value of double-layer capacitance is the largest. This also means that in the electrochemical reaction, the rate of electron transfer when 30mmol of catalytic material is added is about twice that of 20mmol and 40mmol, and the charge movement at the interface is also faster than 10mmol. This shows that under the joint action of the three metals, the amount of P added cannot be too much. Too much will reduce the amount of metal deposition and the electron transfer ability of the material, which will restrict the electron transfer speed in the reaction; too little will fail to achieve the corresponding catalytic effect. Figure 7 This view is also confirmed in (b). The arc radius formed by 10mmol NaH2PO3·H2O is the largest, corresponding to the largest impedance value. The electrocatalyst made of it is not easy to be polarized. Next are 20mmol and 40mmol. In general, finding the optimal doping amount of NaH2PO3·H2O plays an indispensable role in the electrode reaction and is an essential step.
[0084] in accordance with Figure 8 It can be observed that the Ni / Ce / Fe / P sample prepared with 1400 mesh stainless steel mesh as the substrate after 35 cycles of deposition showed a larger electrochemical active area when 30 mmol NaH2PO3·H2O was added as the phosphorus source, which also means that Ni / Ce / Fe / P has a larger active area. Figure 3 In the LSV diagram (b), it can be observed that among the four phosphorus source catalytic electrode materials with different addition amounts, the curve of 30mmolNaH2PO3·H2O is at the bottom, which is closest to the value of 25%Pt / C. When the electrochemical reaction is carried out in 1M KOH solution, when the current density reaches 10mA·cm -2 , the overpotential is 61.6mV. At the same time, in the HER image, a specific range will be provided for measuring ECSA. In the curve obtained during the measurement, the flattest area is found as the center. The curve in this range indicates that the electrode material has not undergone redox reaction. The Faraday capacitance in this range is small. This method is one of the means to obtain non-Faraday current. In this experimental operation, the voltage range selected is about 50mV as the numerical range of the CV graph. According to Figure 8 In (a), it can be more clearly observed that the Tafel slope of the electrode material obtained by electrochemical deposition corresponding to the addition of 30 mmol of phosphorus source is the smallest, which is 34 mV·dec. -1, showing the sample deposited 35 times, using 1400 mesh stainless steel mesh substrate material, adding 30mmolNaH2PO3·H2O as phosphorus source, Ni / Ce / Fe / P itself has excellent HER kinetics, and the charge movement is faster than other materials; when 30mmol phosphorus source is added, the electrochemical reaction rate is faster; when the reaction reaches the same current density, only a small overpotential is required, which means it has a faster electron transfer rate. In summary, the electrode material deposited in the electrolyte solution with 30mmol NaH2PO3·H2O is characterized by a larger electrochemical active area and more active sites; doping with an appropriate amount of P will neither reduce the deposition amount of Ni / Ce / Fe / P trimetallic due to excessive P, nor will the catalytic activity be insufficient due to too little P doping. The appropriate amount of P doping can enhance the catalytic ability of the catalyst.
[0085] The Tafel slope of trimetallic phosphide samples with different scanning numbers (a) and the LSV diagram of trimetallic phosphide samples with different scanning numbers (b) are shown in Fig. 9 .
[0086] Fig.10 What is measured is the stability of the trimetallic phosphide sample in Example 1. The stability is also an important indicator for measuring the ability of a water electrolysis hydrogen evolution catalyst. The present invention adopts a chronoamperometry to test the sample for 24 hours continuously. The test results show that the catalytic ability of the sample has good durability.
[0087] The invention prepares a new electrode material trimetallic phosphide: Ni / Ce / Fe / P by an electrochemical deposition method. In order to find the phosphorus source doping amount with the best catalytic effect, four groups of NaH2PO2·H2O electrolyte solutions with different contents of 10mmol, 20mmol, 30mmol and 40mmol are set to compare the catalytic effects of electrode materials deposited; the electrode materials deposited by stainless steel mesh substrate materials with 600 mesh, 1400 mesh, 1600 mesh and 2000 mesh are used to compare the catalytic effects; four groups of samples with different deposition circles of 14 circles, 28 circles, 35 circles and 42 circles are set, and 1M KOH solution is used. The electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) curve and the like are measured in an electrochemical workstation using a three-electrode system. The measurement results show that the overpotential of the trimetallic phosphide is 20mV less than that of the bimetallic phosphide. The activity can be maintained after continuous operation for 24 hours.
[0088] (1) By comparing the HER graphs, EIS graphs, and CV graphs of samples deposited at 14, 28, 35, and 42 cycles, the double-layer capacitance graph and Tafel slope graph were plotted. The results showed that the electrode material deposited at 35 CV cycles had the best catalytic effect. -2, the overpotential is 61.6 mV, and the Tafel slope is 38.7 mV·dec -1 . It is proved that the catalytic effect of the catalytic electrode under 35CV is the best.
[0089] (2) The electrochemical performance of 600 mesh, 1400 mesh, 1600 mesh, and 2000 mesh stainless steel meshes with a scanning number of 35 was tested. The analysis results showed that the 1400 mesh stainless steel mesh had excellent electrocatalytic hydrogen evolution performance as the substrate material for electrodeposition. When the current density was 10 mA cm -2 , the overpotential is 61.6mV, and the Tafel slope is 41.7mV·dec -1 , proving that the 1400-mesh catalytic electrode has the best catalytic effect.
[0090] The HER graph, EIS graph and CV graph were measured and analyzed by using electrolyte solutions composed of 10mmol, 20mmmol, 30mmol and 40mmol NaH2PO2·H2O, and the Tafel slope graph was drawn. The analysis results show that the electrode material deposited in 30mmol NaH2PO3·H2O solution has the best catalytic effect. -2 , the overpotential is 61.6mV. The arc radius is the smallest in the EIS graph, and it has a faster polarization speed.
[0091] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing trimetallic phosphides, characterized in that: Using stainless steel mesh as substrate, trimetallic phosphides were prepared by electrochemical deposition; The metals in the electrodeposition solution during electrochemical deposition are cerium, iron and nickel.
2. The method for preparing trimetallic phosphides according to claim 1, characterized in that: The molar ratio of cerium, iron, nickel and phosphorus source is 0.75:21.5:30:(10-40).
3. The method for preparing trimetallic phosphides according to claim 2, characterized in that: The electrochemical deposition process adopts cyclic voltammetry, and the voltage is set at -1.2V to -0.6V.
4. The method for preparing trimetallic phosphides according to claim 3, characterized in that: The mesh number of the stainless steel mesh is 600-2000 meshes.
5. The method for preparing trimetallic phosphides according to claim 2, characterized in that: The number of cycles of the electrochemical deposition is 14-42 cycles.
6. The method for preparing trimetallic phosphides according to claim 1, characterized in that: The phosphorus source in the electrolyte during electrochemical deposition is NaH2PO2·H2O.
7. The method for preparing trimetallic phosphides according to claim 1, characterized in that: The process of pre-treating the stainless steel mesh before electrochemical deposition includes the following steps: The stainless steel mesh was cut into 1 cm × 2.5 cm and polished with sandpaper. The polished stainless steel mesh was placed in hydrochloric acid and ultrasonicated for 30 min. Then, it was ultrasonicated with anhydrous ethanol and water for 20 min respectively, and finally dried.
8. The method for preparing trimetallic phosphides according to claim 1, characterized in that: The method also includes a step of performing a drying process after the electrochemical deposition is completed.
9. A trimetallic phosphide, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the trimetallic phosphide according to claim 9 in producing hydrogen by electrolysis of water.
Citation Information
Patent Citations
Fe-Ni-P-RE multi-element alloy coating as well as electro-deposition preparation method and application thereof
CN104561768A
Preparation method of self-supporting ferronickel phosphide / aza-carbon cloth composite electrode
CN110484933A
Nickel-phosphorus composite hydrogen production electrode with foamed nickel loaded and doped with CeO2 as well as preparation and application of nickel-phosphorus composite hydrogen production electrode
CN116575055A